Spectroscopic imaging ellipsometry for thin film detection on uniaxial crystal - Guan, Lichao (2019)
Spectroscopic imaging ellipsometry (SIE) is a powerful technique devoted to the study of optical properties and thickness of thin films by measuring the change in polarization state of light reflected from the surface. SIE measures two quantities (Ψ and Δ ), which represent the amplitude ratio and phase angle of deflection of the p-polarized light and s-polarized light reflected from the sample surface. The SIE measurement of thin film is difficult when the substrate is uniaxial anisotropic crystal for two reasons - firstly the p-polarized and s-polarized components of reflective light are coupled which makes the data processing more complex and secondly an optical model is needed for SIE data processing with the substrate optical constants as known parameters in the model, but the substrate optical constants are not unique when the plane of the optical axis changes. Hence in the measurement of thin film on an anisotropic material using generalized ellipsometry, significant errors due to the complex calculation arise. The best approach is to measure the uniaxial substrate as an isotropic material by adjusting the optical axis in the incident plane. In this paper, the crystal optical axis is determined by rotating the sample using the SIE setup and the incident light is adjusted in the optical axis plane to eliminate the effects of uniaxial substrate. A uniaxial KDP (Potassium Dihydrogen Phosphate) crystal with thin oil film and a bare KDP substrate are prepared. A scheme to determine KDP crystal optical axis is proposed. Finally, the optical constants of the KDP substrate are determined, and the oil film thickness on KDP crystal is measured when the incident light is in crystal optical axis plane.